Making visible the invisible and vice versa. Bodies and organisational arrangements in the Intensive Care Unit - Lusardi, Roberto (Acta Biomedica Atenei Parmensis, 2016)
Background and aims: The effectiveness of the treatments carried out in the Intensive Care Unit (ICU) is guaranteed by a socio-technical ensemble where material resources, scientific knowledge, technological artefacts, social norms, spatial dispositions, and professional practices coexist and constantly interact. This paper intends to penetrate such an ensemble for analysing the moral order produced and maintained in everyday medical practice. Method: The results of a case study, carried out in the ICU of a hospital in the north of Italy between 2006 and 2007 are reported. The study was performed using ethnographic methods: participant observation, ethnographic interviews, and semi-structured interviews. Results: I illustrate how ward organisation and professional practices of medical and nurse staff create and reproduce two dispositions of body centred on the staff’s perception of the therapeutic appropriateness of patients. On one side, there are the bodies that staff expect to get better, and these bodies are exposed through a series of organisational devices and activities in order to make them immediately accessible and available for every type of treatment; on the other side, the bodies of chronic and terminal patients tend to become invisibles in the working practice of the unit. This process does not follow any guideline or protocol but is embodied in informal routine and communicative interactions. Conclusions: The invisibility surrounding certain patients can be seen as strategies for the management of professional conflict and bioethical issues that stem from different interpretations of the degree of severity of the patients’ conditions.